2014
DOI: 10.1021/cm503178j
|View full text |Cite
|
Sign up to set email alerts
|

First-Principles Predictions and in Situ Experimental Validation of Alumina Atomic Layer Deposition on Metal Surfaces

Abstract: The atomic layer deposition (ALD) of metal oxides on metal surfaces is of great importance in applications such as microelectronics, corrosion resistance, and catalysis. In this work, Al 2 O 3 ALD using trimethylaluminum (TMA) and water was investigated on Pd, Pt, Ir, and Cu surfaces by combining in situ quartz crystal microbalance (QCM), quadrupole mass spectroscopy (QMS), and scanning tunneling microscopy (STM) measurements with density functional theory (DFT) calculations. These studies revealed that TMA un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
80
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(90 citation statements)
references
References 56 publications
10
80
0
Order By: Relevance
“…22 Coincidentally, we have observed that trimethylaluminum (TMA) undergoes dissociative chemisorption to form AlCH 3 * (the asterisk designates a surface species) on noble metal surfaces (Pd, Pt, and Ir) in the first Al 2 O 3 ALD cycle using TMA and water at 200°C. 36,37 Zaera et al observed that bis[(N,N′-di-sec-butyl acetamidinate)-Cu] adsorbs dissociatively on Ni(110) surfaces at temperatures between approximately 77 and 177°C; 38 Braun et al reported that ferrocene can even adsorb dissociatively on Au(111) surfaces at temperatures as low as 80 K using low temperature scanning tunneling microscopy (STM). 39 Such dissociative chemisorption of metal precursors on noble metal surfaces seems to be general due to the catalytic nature of noble metals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…22 Coincidentally, we have observed that trimethylaluminum (TMA) undergoes dissociative chemisorption to form AlCH 3 * (the asterisk designates a surface species) on noble metal surfaces (Pd, Pt, and Ir) in the first Al 2 O 3 ALD cycle using TMA and water at 200°C. 36,37 Zaera et al observed that bis[(N,N′-di-sec-butyl acetamidinate)-Cu] adsorbs dissociatively on Ni(110) surfaces at temperatures between approximately 77 and 177°C; 38 Braun et al reported that ferrocene can even adsorb dissociatively on Au(111) surfaces at temperatures as low as 80 K using low temperature scanning tunneling microscopy (STM). 39 Such dissociative chemisorption of metal precursors on noble metal surfaces seems to be general due to the catalytic nature of noble metals.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…This is consistent with very low carbon coverage that was observed during the early stages of TMA adsorption at 300 and 473 K ( Figure 5) and literature reports of CH 4 (methane) and C 2 H 6 (ethane) desorption during exposure of Pd nanoparticles to TMA. 20,56,79 Another route for carbon disappearance could be dissolution of carbon in palladium bulk (Figure 14h). 47 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 Figure 15 shows the TMA adsorption and dissociation mechanisms on Pt(111 Fig SI.3).…”
Section: Pd(111)mentioning
confidence: 99%
“…A detailed understanding of ferrocene adsorption and oxidation, as well as the formation of monolayer thick FeO islands on Pt(111), is developed here using a suite of Ultra High Vacuum (UHV) surface sensitive techniques, whose efficacy has been established in previous studies of vacuum ALD. [38][39][40][41][42] …”
Section: Introductionmentioning
confidence: 99%